Spatial database : residential property system with air pollution index / Mohd Hilmi Jamaluddin - Jamaluddin, Mohd Hilmi (2006)
Over the year. Spatial Database has been an active part of research for more two decades. The principle momentum for research in Spatial Database Management System (SDBMS) arise from the needs of existing applications such as Geographical Information System (GIS) and Computer Aided Design (CAD), Data Warehousing, and NASA's earth observation system, and as well as potential applications. Multimedia Information System (MIS).By means of the technology, GIS offers a convenient mechanism for analysis and visualization which allow a user to have a powerful effect transformation of geographic data. The GIS's analysis operations such as searching, measurement, location analysis, flow analysis, and spatial analysis give the growth of Residential Property System and other multidisciplinary applications. This research began by interviewing and a literature review as to gain the nature thoughtful of the research. By interview with the GIS company in Klang, the spatial data has been gathered and factory list derived from MBSA. All together, a database and web has been constructing and proposed to the supervisor. Subsequent to make analyzing from data collection. Section 26, Shah Alam, Selangor is a selected region in order to fulfill the objectives of this research and project development. Through SDLC in development, the findings are the spatial database has been developed as to hold the residential property data and published it through the GIS also known as web-based online. From beginning to end of thesis reading, it will discuss thoroughly of this development.